2008
DOI: 10.2459/jcm.0b013e32831103c3
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting stents in a patient with favism: is the aspirin administration safe?

Abstract: We describe the case of a 64-year-old patient with glucose-6-phosphate dehydrogenase deficiency who was referred to our hospital because of an acute inferior myocardial infarction.Given the possible risk of acute haemolytic anaemia, aspirin was not given in the acute phase, and the patient was successfully treated by balloon angioplasty of the right coronary artery.After functional and genetic testing showing the presence of the Mediterranean mutation, known to be a class II variant, the patient received oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…There are only a few reports on the long‐term safety of ASA in patients with favism . Moreover, reports are even fewer regarding the long‐term safety and efficacy of DAPT in patients with G6PD deficiency needing PCI with DES, and thus, no official guidelines are available …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only a few reports on the long‐term safety of ASA in patients with favism . Moreover, reports are even fewer regarding the long‐term safety and efficacy of DAPT in patients with G6PD deficiency needing PCI with DES, and thus, no official guidelines are available …”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, reports are even fewer regarding the long-term safety and efficacy of DAPT in patients with G6PD deficiency needing PCI with DES, and thus, no official guidelines are available. 12,13 The limited data available on the safety of ASA in patients with favism and ACS are rather contradictory. Porto et al 12 describe a case of anterior STEMI treated in the acute phase using manual thrombectomy and intracoronary IIb/IIIa glycoprotein inhibition with abciximab without any attempt to implant a stent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of his already mentioned antiplatelet effect, the use of aspirin in association with other drugs that increase the risk of bleeding must be controlled. In addition, aspirin should be used with prudence in the elderly, because of the risk of Reye's syndrome [18] and in individuals with favism, although recent studies have shown a good tolerance to low doses of the drug in these patients [19]. …”
Section: Aspirinmentioning
confidence: 99%
“…To the best of our knowledge, there is only one other report about STEMI in patients with favism, by Rigattieri et al 23) . The incidence of cadiovascular disease in patients with favism seems to be low, and the cardiovascular protective role of this genetic alteration has been hypothesized 24) .…”
mentioning
confidence: 99%